Improve Adult Health Life in Western Sydeny Through Health Promotion Models - Hamzeh Khudeir; DUA’A Khudeir (European Scientific Journal, ESJ, 2017)
This report will focus on a new health development initiative for the Western Sydney Adolescents and their health needs in terms of promoting physical activity and exercise because it helps them live longer and better lives and become more energetic. The target group are fairly sedentary individuals and consume copious amounts of energy dense foods, which are contributing to the burgeoning obesity risk factors in the community. A sedentary lifestyle contributes towards a range of cardiovascular diseases and health problems including heart disease, obesity, high blood pressure, high cholesterol and many types of cancers (Meyer, 2007). Successfully tackling obesity in a health promotion context, is a long-term, large-scale commitment that will require both individual responsibility and action together with a population-based approach, driven by partnerships between governments, businesses, and communities. The current prevalence of obesity in the population has been at least 30 years in the making, and will take considerable time to reverse the trends and its impacts and determinants on health (Roth, 2011). This article will outline the costing requirements and the evaluation methods that will be used in our adolescent obesity health promotion and prevention management strategy. This will be achieved by using a combination of educational and awareness campaigns, public advertising, healthy urban planning, imposing a ban on canteen junk food and establishing a health and wellbeing telephone hotline and social networking group. This will be evaluated for feasibility using cost-benefit analysis to determine whether each strategy or approach is to be implemented or not.